HOW IS E-COMMERCE CHANGING AGRICULTURAL LOGISTICS? - Dustova , Mukhayyo; Makhmutullayeva , Sevinch (THE INNOVATION ECONOMY, 2023)
This research explores the evolving landscape of agrilogistics in the era of e-commerce platforms. The study sheds light on the complex interplay between e-commerce and agriculture, highlighting opportunities and challenges in this dynamic sector.